Exploring online communication about cigarette smoking among Twitter users who self-identify as having schizophrenia. (November 2017) - Hswen, Yulin; Naslund, John A.; Chandrashekar, Pooja; Siegel, Robert; Brownstein, John S.; Hawkins, Jared B.
Abstract: Novel approaches are needed to address elevated tobacco use among people with schizophrenia. This exploratory study examined the frequency, timing, and type of communication about tobacco-related content on Twitter among users who self-identify as having schizophrenia compared with users from the general population. Over a 200-day period from January to July 2016, Twitter users who self-identify as having a schizophrenia spectrum disorder ( n = 203) and a randomly selected group of general population control users ( n = 173) posted 1, 544, 122 tweets. Communication frequency did not differ between groups. Tweets containing tobacco-related keywords were extracted. Twitter users with schizophrenia posted significantly more tweets containing any tobacco-related terms (mean = 3.74; SD = 16.3) compared with control users (mean = 0.82; SD = 1.8). A significantly greater proportion of Twitter users with schizophrenia (45%; n = 92) posted tweets containing any tobacco terms compared with control users (30%; n = 52). Schizophrenia users showed significantly greater odds of tweeting about tobacco compared with control users (OR = 1.99; 95% CI 1.29–3.07). These findings suggest that online communication about tobacco may parallel real world trends of elevated tobacco use observed among people with schizophrenia. By showing that Twitter users who self-identify as having schizophrenia discuss tobacco-related content online, popular social media could inform smoking cessation efforts targeting this at-risk group. Highlights: Posts from Twitter users who self-identify as having schizophrenia were explored. Their communication about tobacco was compared with control Twitter users. Schizophrenia users posted more tweets containing tobacco-related terms. Schizophrenia users had greater odds of tweeting about tobacco. Twitter could inform smoking cessation efforts for people with schizophrenia.